SOIL PHYSICAL QUALITY AFTER NITROGEN FERTILIZERS USE IN IRRIGATED PASTURE OF TIFTON 85 - de Melo, Marina Luciana Abreu; Guimarães, Eduardo Vieira; Silva, Bruno Montoani; da Costa, Édio Luiz; Caixeta, Samuel Petraccone (Scientia Agraria, 2017)
Tifton 85 (Cynodon sp.) is a forage crop widely used for the voluminous production, but it has also the potential to promote preservation or improvement in soil structural quality, when well managed. The aim of this work was to evaluate the soil physical quality in a rotational grazing area of Tifton 85 under irrigation in Prudente de Morais, MG, Brazil, due to the application of mineral and organic nitrogen fertilizers. The treatments included different forms of N supply: 400 kg ha -1 of urea; 400 kg ha-1 of bovine manure; 400 kg ha-1 of urea and manure, in proportion 1:1 and the control, without nitrogen fertilization. The following soil physical quality indicators were determined in the layers 0.0-0.05 m and 0.05-0.10 m after two years of N application: water retention curve, total porosity, macroporosity, microporosity, soil bulk density, available water capacity, bulk soil air capacity, soil matrix air capacity and relative water capacity. There were differences among the treatments, in both layers. In general, the treatments using bovine manure promoted greater water storage and availability, which was related to the increase of the microporosity, due to the organic matter effect. However, these same treatments presented a relative compaction, which was associated to the maintenance of higher soil moistures. It was concluded that, even under the effects of intensive grazing, there was generally adequate soil physical quality, but a special attention is recommended to the soil susceptibility to compaction.